APPLICATION OF k0-INAA TECHNIQUE FOR THE ANALYSIS OF ESSENTIAL AND BENEFICIAL HEAVY ELEMENTS IN SOIL (FUDMA JOURNAL OF SCIENCES, 2023)
The researchers analyzed the essential and beneficial heavy elements in soil that improve plant growth,development and other functions in this study using k0 – INAA technique. The use of k0 – InstrumentalNeutron Activation Analysis (k0 – INAA) technique has become a veritable tool for multi-element analysis.This method has been applied in this present study to assess essential mineral elements and beneficial heavyelements that supports plants growth of fifteen (15) samples collected from Safana, Dan Musa and Kankia,LGAs of Katsina State. The samples were properly prepared together with the standard reference material(NIST Coal Fly Ash 1633b) and were irradiated at a thermal power level of 31.0 kW corresponding to aneutron flux setting of 2.5 x 1011 cm-2 s-1 and 5.0 x 1011 cm-2 s-1 for the outer and inner irradiation channelsrespectively using the Nigeria Research Reactor – 1 (NIRR – 1) at the Centre for Energy Research andTraining, Zaria. After irradiation, the samples were counted using a high-purity germanium detection system(GEM 30195 coaxial detector) and the concentrations of eleven elements (Mg, Ca, Ti, V, Mn, Na, K, Cr, Fe,Co and Zn) from the samples and that of NIST Coal Fly Ash 1633b were measured using the k0 – IAEAprogram. The result of the NIST Coal Fly Ash 1633b was in agreement with that of the certified values. Theconcentrations of the elements measured from the samples shows that these elements are sufficient for plantgrowth, except that some of
Keywords: k0 – INAA, nuclear reactor, essential mineral elements, beneficial heavy elements, plant growth